(untitled) (Northern International Medical College Journal, 2020)
Background : Preeclampsia is associated with maternal and neonatal complications. It has been indicated that increased uric acid might have a predictive role on preeclampsia. Several studies have demonstrated a relation between elevated maternal serum uric acid levels and adverse maternal and fetal outcome. The aim of this study was to find out the association of serum uric acid level between normotensive and pre-eclamptic (PE) patients in third trimester of pregnancy and perinatal outcome. Methodology : A case control study was conducted in the department of the Obstetrics and Gynaecology in Dhaka Medical College Hospital from July 2017 to June 2018. A total number of 100 pregnant women in third trimester of pregnancy attending in Obstetrics and Gynaecology department of Dhaka Medical College Hospital were selected purposively as study subjects. Among them 50 diagnosed cases of preeclampsia were selected as cases with age range of 18-35 years and 50 normal healthy age matched pregnant women as controls. Pregnant women with pre-existing hypertension, diabetes mellitus and renal disease were excluded from the study by history, clinical examination and relevant laboratory investigations. Results : The mean serum uric acid level was found 4.49±1.72 mg/dl in normotensive group and 7.03±1.89 mg/dl in preeclampsia group. Serum uric acid was significantly higher (p<0.05) in pre-eclampsia group than normotensive group. Regarding outcome take home as alive neonate was found 48(96.0%) in normotensive group and 41(82.0%) in preeclampsia group. Early neonatal death was 1(2.0%) in normotensive and 4(8.0%) in pre-eclampsia group. Still birth was 1(2.0%) and 5(10.0%) in normotensive and pre-eclampsia group respectively. Conclusion : Hyperuricemia is most basic and reliable observations in pre-eclamptic pregnancies. While elevated concentrations of circulating uric acid are not uniformly increased in every woman with PE. But hyperuricemia is found in a subset of pre-eclamptic women who had higher risk for maternal and fetal complications. Therefore, measurement of serum uric acid concentration seems to be a useful test to predict maternal and fetal complications in a women with preeclampsia. Northern International Medical College Journal Vol. 11 No. 1 July 2019, Page 419-422